Al Jam‘iyatul Washliyah dan Pelestarian Akidah Ahl Sunnah wa al-Jamā‘ah di Indonesia - Ja'far Ja'far (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2019)
The development of Islam in Indonesia cannot be separated from the role and influence of Islamic organizations. Islamic organizations in this region are usually divided into two; traditionalist and modernist. One of the Islamic organizations labelled as traditionalists is Al Jam’iyatul Washliyah. Studies on Al Washliyah have been carried out, but the research on the role of Al Washliyah in developing the Ahl al-Sunnah wa al-Jamā'ah school has not been carried out and is still neglected. This article aims to examine the role of the Al Washliyah organization in strengthening the Ahl al-Sunnah wa al-Jamā'ah school in Indonesia. By combining library and field studies, this study found that Al Washliyah played an active role in developing the thought of the school through its institution called the Al Washliyah Fatwa Council, while the scholars of Al Washliyah had produced works in theology in line with the framework of Ahl al-Sunnah wa al-Jamā‘ah.